Unearthing Techniques Lecturers Apply to Reflect on Their Teaching Process in Selected Universities in Lusaka and Copperbelt Provinces of Zambia - Namonje, Elizabeth; Halwiindi, Hikabasa; Zyambo, Cosmas; Simui, Francis; Muleya, Gistered (Advances in Social Sciences Research Journal, 2023)
This article explores techniques lecturers apply to reflect on their teaching process in selected universities in Lusaka and Copperbelt Provinces of Zambia. The study was qualitative underpinned with social constructivism worldview. The case study design was used. In this study, data was generated from 32 participants who were purposively selected and were subjected to one-on-one interviews and focus group discussions. The generated data was analyzed using thematic approach. The study revealed that public health lecturers reflect on their teaching process using academic assessment of students, peer reflective teaching, through participatory approaches, getting feedback from the learners, participatory work in the laboratory and action research. The study concluded that although lecturers reflected in and on their teaching, the style of reflection has not been enhanced to the level of them being critical and innovative reflective practitioners. Based on the findings, the study recommends that Education standards officers should continue to maintain standards in Universities and Colleges to control over enrolments and overcrowding in classes so that the lecturers can teach efficiently and effectively so that students can benefit fully from the lecturers.